2018
DOI: 10.1108/aia-08-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

A review of emergency department visits made by youth and adults with autism spectrum disorder from the parent perspective

Abstract: Purpose: Past research has shown individuals with autism spectrum disorder (ASD) visit hospital emergency departments (ED) at high rates. In order to assist individuals with ASD, their families and health care providers to improve ED care, it is important to understand these encounters in greater detail. This study aimed to provide a descriptive summary of the ED experiences of adolescents and adults with ASD, from the perspective of their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Lack of knowledge and difficulty navigating services are identified as significant barriers to accessing appropriate mental health services by autistic people (Lake, Perry, & Lunsky, 2014). Adjustments that may improve access include provision of quiet rooms, removal of potential sensory distractions, and allowance for additional time to articulate problems and concerns (Lunsky, Tint, Weiss, Palucka, & Bradley, 2018). Multi-disciplinary service models incorporating health professionals who have autism knowledge, who are willing to listen and patiently develop a therapeutic alliance with the autistic person, that are co-developed with autistic people, and that take a holistic and lifespan approach are recommended and urgently needed.…”
Section: F) Prevention and Service Accessmentioning
confidence: 99%
“…Lack of knowledge and difficulty navigating services are identified as significant barriers to accessing appropriate mental health services by autistic people (Lake, Perry, & Lunsky, 2014). Adjustments that may improve access include provision of quiet rooms, removal of potential sensory distractions, and allowance for additional time to articulate problems and concerns (Lunsky, Tint, Weiss, Palucka, & Bradley, 2018). Multi-disciplinary service models incorporating health professionals who have autism knowledge, who are willing to listen and patiently develop a therapeutic alliance with the autistic person, that are co-developed with autistic people, and that take a holistic and lifespan approach are recommended and urgently needed.…”
Section: F) Prevention and Service Accessmentioning
confidence: 99%
“…Chun Shing Kwok [ 25 ] reported that cardiovascular disease is the leading cause of death in emergency departments. Lunsky y [ 26 ] reported that the proportion of elderly patients due to cardiovascular diseases is relatively large, and the diseases reported by them include myocardial infarction, heart failure, arrhythmia, angina pectoris, and hypertensive emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…of studies were from Canada, 14,29,30 two (29%) were from Australia, 31,32 and one (14%) from the USA. 33 Most were conducted in pediatric specific EDs (n = 5, 71%).…”
Section: Dovepressmentioning
confidence: 99%
“…The mean year of publication was 2019, with the majority (71%) of studies published after 2016. Three studies were classified as quantitative design (n = 3, using cross-sectional surveys 30,31,33 ), three studies were classified as qualitative design (descriptive phenomenology, 32 grounded theory, 14 interpretive description 34 ) and one as a mixed-method design, 29 utilizing interviews, journey mapping and surveys. Cumulatively, there were 523 participants in the included studies (note overlap in participants from three studies 7,14,15 ), ranging from 14 to 421 across studies.…”
Section: Dovepressmentioning
confidence: 99%